Strategic foresight : an introductory guide to practice - Schwarz, Jan Oliver (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Organizations today are being challenged to make sense of changes in environments that, now more than ever, are described as VUCA (volatile, uncertain, complex and ambiguous). They are also being driven to understand how the future will evolve and what impact it will have not only on the organizations themselves, but also on industries and societies. In recent decades a field has emerged to support organizations in addressing these challenges: strategic foresight. This book is a comprehensive introduction to strategic foresight. It presents a history of the field and explains the main principles in thinking about the future. The book describes how organizations can apply strategic foresight, and explains how it relates to other fields such as strategy, innovation and leadership, highlighting the relevance of strategic foresight not only for organizations but also for individuals, particularly managers and leaders. Grounded in the theoretical foundations of strategic foresight, the book reflects the latest academic research and explores practical applications in different contexts. It draws on more than two decades of experience that the author has in the field as a researcher, a consultant and in the corporate context. This is essential reading for managers and leaders of public and private organizations who want to establish strategic foresight practices, as well as students of foresight and managers in the fields of innovation, research & development and marketing"--
Keywords: Strategic planning; Organizational change; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Leadership